Global organic products market - Vlahović, Branislav; Puškarić, Anton; Maksimović, Branka (Economics of Agriculture, 2010)
The increased demand for food in the world has caused the development of intensive agriculture that is based on the use of considerable amount of chemical substances. The high level of use of fertilizers and plant protection substances damages the environment and has a bad impact on the food quality, whose repercussions can often be felt on environment and human health. In contrast to conventional agricultural production, healthy safe food is produced within the system of organic farming and processing. This type of food is completely grown and produced without synthetic substances (mineral fertilizers, pesticides, plant growth stimulators, hormones, etc) and genetically modified organism (GMO). The production of healthy food currently has an upward trend worldwide, and it is the result of constant demand for such products. There are attempts to initiate the use of healthy food in nutrition and thus contribute significantly to human health and environment protection. There is, however, a question arising of whether global economic crisis is likely to reduce demand for organic products.